COVID-19 and Inflammatory Markers - Balta, Sevket; Balta, Ilknur (Current Vascular Pharmacology, 2022)
Coronavirus disease-2019 (COVID-19) causes mild illness to serious infection with lung involvement, thrombosis, and other complications potentially resulting in fatal outcomes. Recognised inflammatory biomarkers play important roles in managing patients with COVID-19; for example, diagnosis, follow-up, assessment of treatment response, and risk stratification. Inflammatory markers in COVID-19 disease were analysed in two categories. Well-known inflammatory markers include complete blood count, C-reactive protein, albumin, cytokines, and erythrocyte sedimentation rate. Asymmetric dimethylarginine, endocan, pentraxin 3, serum amyloid A, soluble urokinase plasminogen activator receptor, total oxidant status and total antioxidant status, and galectin-3 are considered among the emerging inflammatory markers. This brief narrative review assesses the relationship between these inflammatory markers and COVID-19 infection.
Keywords: inflammation